On the Institutionalization of Congress(es) in Latin America and Beyond - Valeria Palanza; Carlos Scartascini; Mariano Tommasi (Inter-American Development Bank (IDB), 2012)
This paper proposes an agenda for the study of the determinants and the processes by which strong policymaking institutions emerge, with emphasis on the most central democratic institution: the legislature. It reviews extant theories of institutionalization, and proposes further ways of specifying and studying the concept. It emphasizes the notion that investments and beliefs are the driving force of Congress institutionalization and of its relevance in the policymaking process. Making use of several indicators of Congress institutionalization, it provides evidence suggesting that Congress institutionalization has an impact on the qualities of public policies and on economic and social development outcomes. It also explores some 'constitutional' factors that may promote Congress institutionalization. Given that a central theoretical argument of this paper is that the institutionalization of legislatures is a process that includes various self-reinforcing dynamics, the paper also undertakes the preliminary steps in developing a comparative case study of the evolution of Congress institutionalization in two Latin American countries: Argentina and Chile.
Keywords: D70; D72; H0; 330